DESAIN KENDALI KECEPATAN MOBILE ROBOT EMPAT RODA MEKANUM BERBASIS INVERSE KINEMATICS DAN PI ANTI WINDUP PADA KONTES ABU ROBOCON 2023 - Asyfia, Syifa Nurul; Abdul Aziz, Arif; Mulkan Rodiana, Irham (Perpustakaan Universitas Telkom, 2024)
ABU Robocon is a robotics competition in Asia – Pacific organized by the Asia-Pacific Broadcasting Union (ABU). In 2023, ABU Robocon is holding a contest with the theme